{6,6 `-Dibromo-4,4 `-dichloro-2,2 `-[o-phenylenebis(nitrilomethylidyne)]diphenolato}nickel(II) - Ali, A.; Abdullah, N.; Maah, M.J.; Lo, K.M. (International Union of Crystallography, 2010)
In the title complex, [Ni(C(20)H(10)Br(2)Cl(2)N(2)O(2))], the Ni(II) ion is coordinated by two phenoxy O atoms and two imino N atoms of the tetradentate ligand, forming a slightly distorted square-planar environment. The molecule is essentially planar, with an r.m.s. deviation of 0.088 angstrom for the mean plane defined by all non-H atoms in the molecule.